Water-soluble NHC-Cu catalysts: applications in click chemistry, bioconjugation and mechanistic analysis - Velazquez V. H. Velazquez Heriberto; Garcia Ya. R. Yara Ruiz; Vandichel M. Matthias; Madder A. Annemieke; Verpoort F. V. K. Frensis Valter Kornelius (2015, 2015)
Title screen